Tourism in the Era of Covid-19 and Its Impact on the Environment - Rafał Nagaj; Brigita Žuromskaitė (Energies, 2021)
The Covid-19 pandemic has affected all areas of socio-economic life around the world. Its impact concerns not only the health system and the health of the population, but also the economy. Tourism is one of the sectors hardest hit by the restrictions imposed by governments in the wake of the pandemic. The pandemic has resulted in restrictions and limitations on movement and travel, covering both domestic and international tourism, which raises the question of have these restrictions imposed on tourist activities also caused an environmental impact? The aim of this article is to examine what impact the COVID-19 pandemic has had on the environmental issues within the tourism sector in the Central and Eastern European (CEE) region. The research task is to investigate whether this impact has changed in the pandemic era compared to previous years, and whether it has been positive or negative. The research method is multiple regression analysis. The results of the study indicated that the COVID-19 pandemic caused a decrease in greenhouse gas emissions from tourism in all CEE countries. Such decreases are both relative to 2019 and the estimated level of emissions that would be achieved if the countries surveyed achieved economic growth in 2020 consistent with the European Commission’s projections for that year. The scale of the impact varies from country to country, while the relationship between tourism development and pollution levels is positive.